The impact of the United States veto to Huawei on Wall Street - Ordinola Valdez, Andrea Carmen Lidia (2019)
Objective: Describe the impact of the United States veto on the Chinese company Huawei and that has led to the decline in stock market indices on Wall Street. Method: It is a type of quantitative, explanatory causal investigation based on the quantiﬁcation and statistical analysis of ﬁnancial time series of ﬁnancial assets that are listed on the Stock Exchange of the United States of America, in the period of the month of May 2019, focusing mainly on the fall of the stock indexes on Monday, May 20, 2019. Results: The selected sample was made up of eight representative companies, commercially related to the Huawei company, which are part of the Selective Index of the Stock Exchange of the United States of America, showing the relationship they have between them and the eﬀects they have suﬀered as a result of the veto and on the other hand, the main stock market index of globalized ﬁnancial markets has been selected to observe, in the period under analysis, the eﬀects of the event and the relationship they show between ﬁnancial markets. Conclusions: of the relationships shown between American companies, suppliers of Huawei, signiﬁcant relationships have been observed with each other, except with Qualcomm. And on the other hand, the relationship of eﬀect on the relationship that exists in the response that the markets have given in the period of the event under analysis has been observed, appreciating the decrease in the respective quotes.